Model Pembelajaran Discovery Berbasis Blended Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Kimia Mahasiswa - Nurhamidah, Nurhamidah; Amida, Nadia; Elvia, Rina (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Indonesia is one of the countries affected by the Covid-19 outbreak, where thisÂ situation greatly affects all aspects of life, including the field of education. TheÂ learning process is carried out online or in a network to minimize the spread ofÂ this virus, which makes learning effectiveness less than optimal, especially forÂ material in the field of science. Selection of the right strategy and match theÂ material is very necessary. The purpose of this study was to see the activities andÂ learning outcomes of students using a blended learning-based discovery modelÂ on the subject of the Basic Laws of Chemistry. This research is a classroomÂ action research conducted in two cycles. The research subjects were 26 studentsÂ of the Biology Education Study Program in the first semester of the 2021/2022Â class. The research data were obtained through observation sheets and cognitiveÂ tests using a test instrument in the form of a posttest. Based on the data analysis,Â it shows that the activities and student learning outcomes have increased fromÂ 54.62% and 66.25 in the first cycle to 87.69% and 80.48 in the second cycle. TheÂ students’ understanding of the learning materials has included very goodÂ criteria.